DEVELOPMENT MECHANISMS OF CHRONIC HEART FAILURE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Today, people around the world die from many different dangerous diseases, the main ones of which are heart diseases. You will be able to get more and more complete information about heart failure disease, its occurrence, symptoms, origin, diagnosis, prevention and treatment. This article provides information about the mechanisms of development of chronic heart failure.